An analysis of syntactic code mixing used by male and female students in speaking fluency - Ike Dian Puspita Sari (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2018)
Acquiring speaking skill does not only consider the accuracy, but also the fluency. Hence, in doing conversation, somehow people mix the L2 with their L1. This research focuses on analyzing code mixing used by 12 male students and 35 female students as the sample. The data were taken from their presentation. The data classified based on lexical units and code mixing categories. The result shows that there were quite different frequencies of code mixing used by male and female students. Female students tend to mix their L2 with L1 modifier. Based on the categorization of the code mixing data, alternation is mostly used by female students. However, male students prefer to use insertion.